Post-Discharge Mortality and Rehospitalization among Participants in a Comprehensive Acute Kidney Injury Rehabilitation Program. Issue 9 (30th September 2021) - Singh, Gurmukteshwar; Hu, Yirui; Jacobs, Steven; Brown, Jason; George, Jason; Bermudez, Maria; Ho, Kevin; Green, Jamie A.; Kirchner, H. Lester; Chang, Alex R.
Visual Abstract: Abstract : Key Points: Using innovative, patient-centered interventions, 68% of eligible high-risk patients with AKI were enrolled and all came to nephrology follow-up. Participation was associated with improvement in 30-day postdischarge rehospitalization and mortality, with similar 90-day trends. The interventions present a roadmap for improving enrollment in AKI randomized controlled trials and should be tested further. Background: Hospitalization-associated AKI is common and is associated with markedly increased mortality and morbidity. This prospective cohort study examined the feasibility and association of an AKI rehabilitation program with postdischarge outcomes. Methods: Adult patients hospitalized from September 1, 2019 to February 29, 2020 in a large health system in Pennsylvania with stage 2–3 AKI who were alive and not on dialysis or hospice at discharge were evaluated for enrollment. The intervention included patient education, case manager services, and expedited nephrology appointments starting within 1–3 weeks of discharge. We examined the association between AKI rehabilitation program participation and risks of rehospitalization or mortality in logistic regression analyses adjusting for comorbidities, discharge disposition, and sociodemographic and kidney parameters. Sensitivity analysis was performed using propensity score matching. Results: Among the high-risk patients with AKI who were evaluated, 77 of 183 were suitable for inclusion. Out of these, 52 (68%) patients were enrolled and compared with 400 contemporary, nonparticipant survivors of stage 2/3 AKI. Crude postdischarge rates of rehospitalization or death were lower for participants versus nonparticipants at 30 days (15% versus 34%; P =0.01) and at 90 days (31% versus 51%; P =0.01). After multivariable adjustment, participation in the AKI rehabilitation program was associated with lower risk of rehospitalization or mortality at 30 days (OR, 0.41; 95% CI, 0.16 to 0.93), with similar findings at 90 days (OR, 0.52; 95% CI, 0.25 to 1.05). Due to small sample size, propensity-matched analyses were limited. The participants' rehospitalization or mortality was numerically lower but not statistically significant at 30 days (18% versus 31%; P =0.22) or at 90 days (47% versus 58%; P =0.4). Conclusions: The AKI rehabilitation program was feasible and potentially associated with improved 30-day rehospitalization or mortality. Our interventions present a roadmap to improve enrollment in future randomized trials.